Pengaruh Ukuran Perusahaan, Profitabilitas, Keputusan Investasi, dan Kebijakan Dividen Pada Nilai Perusahaan - Rizal, Vonny; Stefanny, Stefanny; Novianty, Henny; Angelieca, Angelieca; Tantowi, Cindy; Intan Purba, Mas (E-Jurnal Akuntansi, 2019)
The purpose of this study is to determine the significance of the effect of company size, profitability, investment decisions, and dividend policy on the value of corporate companies using industrial companies basic and chemicals found on the Indonesian stock exchange which has a population of 69 companies. The approach taken in this study is a quantitative approach, this type of research uses explanatory and causal or causal research characteristics. Types of data collection in the documentation and sampling obtained by 14 companies. Based on the results of company size, profitability, investment decisions and dividend policy in a multiparty-together have a significant effect on firm value. Based on the results partially shows that size company does not affect and is not significant top value of the company, profitability has a significant and significant effect on firm value, investment decisions have no effect on firm value, and dividend policy has a positive and significant effect on firm value. Keywords : Company Size; Profitability; Investation; Dividend.